An Introduction to Immune System with Special Focus on Vaccines for SARS-CoV-2: Part I - Shimray, Chong; Shirol, Shrishail E (SCHOOL SCIENCE, 2021)
COVID-19, the deadly pandemic caused by the coronavirus, SARS-CoV-2 hit the world hard but at the same time brought out the never-seen-before capabilities and capacities of the scientific community, the manufacturing companies and other stakeholders as the world engaged in its search for a vaccine to subdue the virus. Keeping the nature of COVID-19 pandemic and its impact on the immune system in view, this paper, the first part of the two-part article, attempts to provide a broad idea on a the various aspects related to immune system such as what pathogens do to our body and how our immune system works. The sequence of events that happens during SARS-CoV-2 will also be discussed in brief